Kuroza: A Relaxing 3D Game - sezali, aida; kamarudin, noraziahtulhidayu (Applied Information Technology And Computer Science, 2023)
This application is a relaxing desktop-based game that provides meditating elements, such as a 3D beautiful fairy-like forest adventure with calming audio to give off the ambiance of a fantasy world that will bring out a dreamy and imaginary state of mind for users. This project would be targeting a group of university graduates with an average age of 20s and interested in playing games for their stress relief. Therefore, the MDLC methodology is used to develop this game. According to the findings of the alpha testing, the application performed as predicted in each of the test categories. The beta testing which comprised targeted users and a scalar questionnaire show that 100% of respondents choose above-average scalar (4-5) indicating that the app is useful and engaging, as well as acceptable for undergraduate students to play as a relaxing game. There are more things, however, to be improved in the future.